Ukrainian in the United Kingdom: language use, attitudes, ideologies and identities in the Ukrainian community - Harrison, Katie (2020)
This thesis is the first detailed sociolinguistic examination of the Ukrainian community in the United Kingdom. It explores the linguistic repertoires, language practices, and language attitudes and ideologies of community members, as well as the perceived role of language in the formation of identity, and factors affecting the intergenerational transmission and maintenance of the heritage/community language. A mixed methods approach was employed, drawing on a combination of quantitative and qualitative data collected through three complementary methods: questionnaires, semi-structured interviews, and ethnographic observations in a Ukrainian complementary school.